Laticíferos são incomuns em Acalyphoideae? Contribuições da anatomia foliar para taxonomia de Euphorbiaceae - Mouzella, Clara Prandi (Universidade Federal de Viçosa, 2020)
Laticíferos são incomuns em Acalyphoideae? Contribuições da anatomia foliar para taxonomia de Euphorbiaceae. Orientadora: Renata Maria Strozi Alves Meira. Coorientadora: Maria Beatriz Rossi Caruzo. Euphorbiaceae, uma das maiores e mais diversas famílias de eudicotiledôneas, é organizada nas subfamílias Acalyphoideae, Crotonoideae e Euphorbiaceae. Látex é comum em Euphorbiaceae, com exceção de Acalyphoideae cujas cerca de 1.800 espécies são predominantemente não latescentes. Espécies pertencentes à quatro tribos de Acalyohoideae foram analisadas para a detecção de laticíferos em seções longitudinais e transversais do pecíolo e lâmina foliar. Histoquímica e ontogenia do ápice meristemático foram realizadas em espécies de Acalypha. Laticíferos foram observados nas 38 espécies dos 9 gêneros avaliados, sendo constituídos por células alongadas, de citoplasma denso e multinucleadas. Borracha, proteínas, mucilagens e grãos de amido foram detectados pelos testes histoquímicos. Os laticíferos são do tipo não articulados e ramificados, conforme detectado na análise ontogenética em Acalypha accedens, A. brasiliensis e A. poiretii. Nossos resultados demonstraram que laticíferos não são incomuns em Acalyphoideae, contrapondo a literatura. Essa característica deve ser considerada em estudos que visem avaliar como se deu o surgimento e evolução de laticíferos em Euphorbiaceae. Palavras-chave: Látex. Tribo Acalyphaea. Tribo Caryodendreae. Tribo Chrozophoreae, Tribo Plukenetieae

Euphorbiaceae is one of the largest and most diverse families of eudicotyledons. Although many of its species have never been studied in terms of their use, phenology and chemical composition, there are species of recognized economic importance attributed to secondary compounds, such as some constituents of latex. Acalyphoideae is the largest subfamily of Euphorbiaceae, with 1,500 predominantly non-latent species. Species from four tribes were analyzed for the detection of laticifers in longitudinal and transversal sections of the petiole. Histochemistry and ontogeny of the meristematic apex were performed on Acalypha species. Laticifers were observed in the 38 species of the 9 genera evaluated, consisting of mutinucleate elongated cells of dense cytoplasm. Rubber, proteins, mucilage and starch were detected by histochemical tests. Laticifers are non-articulated and branched, as detected in the ontogenetic analysis in Acalypha accedens, A. brasiliensis and A. poiretii. Our results demonstrate that laticifers are uncommon in Acalyphoideae, contrasting the literature. This characted must be considered in studies that aim to evaluate how the appearance and evolution of laticifers in Euphorbiaceae occurred. Keywords: Latex. Tribe Acalyphaea. Tribe Caryodendreae. Tribe Chrozophoreae. Tribe Plukenetieae
Are laticifers uncommon in Acalyphoideae? Contributions of leaf anatomy for the taxonomy in Euphorbiaceae
Keywords: Acalyphoideae - Secreção; Acalypha; Anatomia Vegetal